The Educational Situation Quality Model: A New Tool to Explain and Improve Academic Achievement and Course Satisfaction - Doménech-Betoret, Fernando; Gómez-Artiga, Amparo; Abellán-Roselló, Laura (Frontiers in Psychology, 2019)
Students’ academic achievement is a major concern among countries. Governments spent a lot of money on education to improve students’ competences at all levels of education. Despite the enormous amount of money invested and the reforms made to curricula in many countries in recent years, these measures are not generally producing the desired results according to the data of International Performance Measurement programs for students (e.g. Program for International Student Assessment-PISA by OECD). Given the importance of this issue, this article presents an instructional-motivational model developed in the last decade to explain and improve students’ learning outcomes, e.g. academic achievement and course satisfaction, entitled the “The Educational Situation Quality Model” (MOCSE, acronym in Spanish). Unlike other educational models, MOCSE offers an integrative teaching-learning approach to explain learning outcomes. By taking the educational setting as a unit of analysis, this proposal introduces a new perspective into the existing literature to predict students’ achievement and course satisfaction by combining contributions from relevant psycho-educational theories, such as: “The Job Demands-Resources Model”, “The Expectancy-Value Theory”, and “The Achievement Goal Theory”. Besides being a conceptual framework to guide research, it also provides a methodological way to improve learning outcomes. In this article we first briefly explain the main model’s characteristics and functioning from the student perspective and, second, based on the MOCSE, we offer some keys for teachers to improve academic achievement and students’ course satisfaction for a specific curricular subject. Finally, future proposals and challenges are discussed. Questionnaires are provided in the annex.